2023
DOI: 10.1021/acs.nanolett.2c02944
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Amplified Spontaneous Emission by Electric Field in CsPbBr3 Perovskites

Abstract: Perovskite gain materials can sustain continuous-wave lasing at room-temperature. A first step toward the unachieved goal of electrically excited lasing would be an improvement in gain when electrical stimulation is added to the optical. However, to date, electrical stimulation supplementing optical has reduced gain performance. We find that amplified spontaneous emission (ASE) in a CsPbBr3 perovskite light-emitting diode (LED) held under invariant subthreshold optical excitation can be turned on/off by the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…[ 28 ] The loaded electric field leads to the drift of these ionic defects to the surface of the film, decreasing trap density in the bulk and surface region (Figure 5a,b). [ 18 ] This would result in PL enhancement. On the other hand, the small amount of injected charges can also passivate the defects at the surface of the film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] The loaded electric field leads to the drift of these ionic defects to the surface of the film, decreasing trap density in the bulk and surface region (Figure 5a,b). [ 18 ] This would result in PL enhancement. On the other hand, the small amount of injected charges can also passivate the defects at the surface of the film.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17] In addition, by appropriately designing the device structure, the reduced trap density at the bulk region by positive and negative ion drifting toward the interface of CsPbBr 3 /hole transfer layer and CsPbBr 3 /electron transfer layer can lower amplified spontaneous emission (ASE) threshold. [18] Besides, it is found that the injected charges can also cure some defects. [19] In addition to 3D perovskite, two-dimensional (2D) perovskite is also a big family of perovskite materials for various optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…When the optical pulse arrives 10 ns into the electrical pulse, emission at the laser line is quenched, presumably due to the buildup of heat. The fact that a few ns timing difference separates assistance from quenching indicates that these observations are not related to field-induced ion migration, which alters laser threshold on a much longer time scale (i.e., commensurate with the time average of the electrical pulse train) …”
mentioning
confidence: 97%
“…The fact that a few ns timing difference separates assistance from quenching indicates that these observations are not related to field-induced ion migration, which alters laser threshold on a much longer time scale (i.e., commensurate with the time average of the electrical pulse train). 13 The dependence of the lasing assist on electrical pulse amplitude for an optimally delayed optical pulse is more nuanced (Figure 4b). Although the stimulated emission signal is enhanced on average relative to optical-only pumping over the 30−50 V range, the signal is volatile.…”
mentioning
confidence: 99%